Reproductive management in large dairy herds - Juan S. Vélez (Universidad de Antioquia, 2017)
Record keeping and the evaluation of records are paramount for a successful reproductive management program in a large dairy herd. A variety of reproductive measurements as tools to evaluate reproductive performance are analyzed throughout this presentation. The author discusses different methods of heat detection including their pros and cons. The relationship between general cow management, health, and reproduction are also discussed in this presentation.